The potential of chatGPT in digital learning: A Review - Purnamasari, Lora (RADINKA JAYA UTAMA PUBLISHER, 2023)
Digital education is an activity that monitors developments in the digital world in everyday life. increase literacy, develop critical thinking abilities and skills. Digital education functions as a digital reference for students to guide their learning activities. The aim of this research is to reviewing one of the digital learning resources for students. The research design uses high-quality literature from mature articles. proceedings, which are currently available on Google Scholar for 2019–2022. The research results show that the use of GPT chat as a reference source for learning students' intellectual tasks. Additionally, many GPT Chat user interface issues were also mentioned. In education, this applies to both positive and negative damping contributions. GPT chat is useful for learning, especially as a substitute for one of the digital learning resources for students.